The Overton window [compact disc, unabridged] - Beck, Glenn (Simon & Schuster Audio, 2010)
An unprecedented attack on U.S. soil shakes the country to the core and puts into motion a frightening plan, decades in the making, to transform America and demonize all those who stand in the way. Exposing the plan and revealing the conspirators behind it, PR executive Noah Gardner hatches his own plan to save both the woman he loves and the individual freedoms he once took for granted.